Learning Object: An Effective E-Learning Tool for Computer Program - M. Shahidur, Rahman; M. Khalad, Hasan; M. Zafar, Iqbal (INTI International University, 2007)
E-learning is an effective and efficient means for learning in recent years. Content is one of the key aspects of e-learning where quality plays the main role. This paper concentrates on the qualitative features required for an effective e-learning tool and demonstrates the potential of interactive visualization tools developed under the Codewitz Asialink project for teaching and learning computer programming techniques. The visualization aids are then integrated with the programming courses. Survey on the use of visual aids in the classroom or independently by the students has shown that the students can learn the programming techniques more effectively than the traditional learning approach.